Evaluasi Penerapan CPPB-IRT Industri Rumah Tangga Pangan (IRTP) Minuman Tradisional di Desa Mekarharja - Romada Rezki (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Food safety and quality are a human right for every human being, including food produced by the Home Industries. One of home industries in Mekarharja village is IRTP Pak Haji Maksum. This IRT makes traditional drinks in powder or liquid form, but no product has a marketing authorization yet. One of the appropriate marketing authorization for this IRTP is the PIRT distribution permit from Public Health Office. BPOM has established guidelines for Good Food Processing for IRT (CPPB-IRT). Observation in the production process at the IRT is done to compare the current real conditions with good conditions based on CPPB-IRT. The results of these observations are in the form of 1 minor finding, 3 serious findings, and 3 critical findings. The serious findings on this IRTP are related to facilities for hand washing, employee habits, and production documents. Critical findings on this IRTP are related to food safety education that has not been followed and does not yet have a food label. IRTP Pak Haji Maksum is not included in the category of IRTP that is eligible for PIRT because it is still at level IV in the IRTP classification based on CPPB-IRT findings.